(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study aimed to Formulation, Development and Evaluation of Solid Lipid Nanoparticle for the Chlorthalidone Antihypertensive Drug. The solid lipidnanoparticles(SLN’s)aresubmicroncolloidalcarrierswhicharecomposedofphysiologicalli pid,dispersed in water or in an aqueous surfactant solution. SLNs were prepared by the Hot Homogenization Method. The effect of formulation variables, viz. Different glyceryl monostearate ratio, difference stirring speed, concentration of surfactants using Design of experiments (DOE). Formulation was characterized by different evaluation parameters. Chlorthalidone SLN were evaluated for entrapment efficiency, drug content, particle size, zeta potential, in vitro drug release. The Chlorthalidone -loaded optimized SLN formulation was prepared by setting the formulation factors of drug: glyceryl monostearate ratio of (1:0.5), volume of internal phase 5 ml, volume of external phase 30 ml, surfactant concentration (5% w/v) homogenization speed of 1000 rpm, and homogenization time of 90 minutes. The optimized formulation was subjected to differential scanning calorimetry, Fourier transform infrared spectroscopy, and scanning electron microscopy study. Conclusively, Chlorthalidone-SLNs were successfully formulated with higher drug entrapment and could serve as promising delivery for poorly solubledrug.